Adaptative Mechanisms of Halophytic Eutrema salsugineum Encountering Saline Environment - Li, Chuanshun; Duan, Chonghao; Zhang, Hengyang; Zhao, Yaoyao; Meng, Zhe; Zhao, Yanxiu; Zhang, Quan (Frontiers in Plant Science, 2022)
Salt cress (Eutrema salsugineum), an Arabidopsis-related halophyte, is naturally adapted to various harsh climates and soil conditions, thus it is considered as a desirable model plant for deciphering mechanisms of salt and other abiotic stresses. Accumulating evidence has revealed that, compared with Arabidopsis, salt cress possesses more tightly closing stomata and more succulent leaves during extreme salt stress, a noticeably higher level of stress-associated transcripts in unstressed plants, and they are induced rapidly under stress, as well as constitutively higher levels of proline, inositols, sugars and organic acids. In this review, we systematically summarize the research on the morphology, physiology, genome, gene expression and regulation, protein and metabolite profile of salt cress under salt stress. We emphasize the latest advances in research on the genome adaptive evolution encountering saline enviroments, and epigenetic regulation, and discuss the mechanisms underlying salt tolerance in salt cress. Finally, we discuss the existing questions and opportunities for future research in halophytic Eutrema. Together, the review fosters a better understanding the mechanism of plant salt tolerance, and provide a reference for the research and utilization of Eutrema as a model extremophile in the future. Furthermore, the prospects for salt cress applied to explore the mechanism of salt tolerance provide a theoretical basis to develop new strategies for agricultural biotechnology.